Análise da agricultura familiar no Município de Irauçuba, segundo a sua capacidade adaptativa à seca, a partir das tecnologias de captação e armazenamento da água - Oliveira, Jamille Albuquerque de (2014)
According to the Food and Agriculture Organization of the United Nations (FAO), 80% of farms in Latin America and the Caribbean are family farms, including more than 60 million people, becoming an important source of labor. Despite the economic and social importance of family farms, the majority of workers employed in this sector are faced with obstacles of structural and economic order even if assisted by various public policies. In the case of Ceará, are allied with socioeconomic vulnerability environmental problems resulting from the instability of the rainfall, environmental degradation and the progress of desertification processes. From the perspective of family agriculture, adaptation measures to problems arising from climate instability would favor living with drought and reduce local socioeconomic problems. This analysis of family farming in the municipality of Irauçuba identifies a set of interventions that could be classified as adaptive: social technologies - already seeking to increase the resistance of farmers to drought. For this it was proposed with this study: to investigate socioeconomic characteristics of farmers in the municipality; analyze how the drought affects farmers in the municipality of Irauçuba; identify adaptive to the phenomena of drought measures related to water resources, implemented in the properties of family farming in the municipality of Irauçuba and verify that the phenomena of drought adaptive measures may be associated with quality of life of family farmers. Considering the occurrence of heterogeneity among farmers surveyed, it was decided to group them into three classes (lower levels, intermediate levels and higher levels) according to their similarity to the Quality of Life Index (QLI). A greater proportion of them are in class with lower levels of quality of life. An even larger aggregation of indexes for each dimension points a Quality of Life Index (QLI) average of 0.443. Drought is suggested as a factor reducing the quality of life by 66.3% of respondents. The results achieved in this research indicated low level of adoption of social technologies, seen as simple, cheap and easily accessible. The absence of public policies towards the adoption of adaptive measures, observed in the city, can be seen as one of the factors responsible, given that access to technologies depends on encouragement, financial support, guidance, differentiated education in rural schools and practical instruction. We observed a statistically significant association between quality of life and the use of technologies spout tank, pond, traditional patriarch and underground dam. What does it mean that the use of these water capture and storage technologies are associated with higher indices of quality of life, so it can provide small farmers of Irauçuba a better quality of life.